Fraus legi between Cicero and the classical jurisprudence - Trisciuoglio, Andrea (Ciceroniana On Line, 2023)
Cicero’s Pro Plancio discusses the specific procedure for selecting judges in light of the lex Licinia of 55 BC on the crimen sodaliciorum. Through a close reading of those passages, the paper seeks to confirm the thesis first put forward by Fascione, according to which the jurists of the classical age drew inspiration from the theoretical reflection on the fraus legi developed in relation to the public legislation of the republican era.